The Medicine in the Hippocratic and post-Hippocratic age: - - Lazarević, Tatjana; Kovačević, Zoran; Janićijević Petrović, Mirjana A.; Ljujić, Biljana; Glišić, Miloš; Janićijević, Katarina (Vojnosanitetski pregled, 2022)
-
Keywords: greece; history, ancient; history of medicine; physicians; therapeutics.